2012
DOI: 10.3144/expresspolymlett.2012.59
|View full text |Cite
|
Sign up to set email alerts
|

Structure-properties relationships of polyhedral oligomeric silsesquioxane (POSS) filled PS nanocomposites

Abstract: Abstract. The polyhedral oligomeric silsesquioxane (POSS) additivated polystyrene (PS) based nanocomposites were prepared by melt processing and the structure-properties relationships of the POSS-PS systems were compared to those of the neat PS. In order to investigate the effect of these structural parameters on the final properties of the polymer nanocomposites, five different kinds of POSS samples were used, in particular, POSS with different inorganic cage and with different organic pendent groups. The rhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 24 publications
2
35
0
Order By: Relevance
“…Tg for various polystyrene-POSS systems prepared with particles present during polymerization [33] or by melt blending [35]. In this case, no effect of POSS on Tg was observed.…”
Section: Co-polymerizationmentioning
confidence: 82%
“…Tg for various polystyrene-POSS systems prepared with particles present during polymerization [33] or by melt blending [35]. In this case, no effect of POSS on Tg was observed.…”
Section: Co-polymerizationmentioning
confidence: 82%
“…The analysis of the trend of viscosity versus frequency for the PE/1POSS suggests that unbound POSS molecules act as a plasticizer of PE, thus increasing free volume in the melt; this last effect leads to lower G and G with respect to the neat matrix. 9 The DCP loading causes cross-linking and branching of the polymer matrix as deducible by the viscosity values and G slope increase in the low-frequency range as compared to the neat polymer matrix. Finally, comparing the rheological behavior of the PE/DCP/1POSS hybrid and PE matrix, it can be inferred that in the loaded system two opposing effects occur: The physically dispersed unreacted POSS leading to lower viscosity and moduli values and, on the other hand, grafted POSS molecules, affecting polymer chain mobility, result in higher viscosity and moduli.…”
Section: Resultsmentioning
confidence: 99%
“…8 The POSS incorporation in polymer matrices by using physical blending (no reactive melt mixing) is a fast, adaptable, and profitable way to obtain hybrid nanocomposites, but the successful dispersion of POSS depends on the interactions, which are Van der Waals, hydrogen, and polar bonding, between POSS molecules and polymers. [9][10][11][12][13] Since a uniform POSS incorporation into some polymers leads to enhancements in thermal stability, mechanical properties, and reduces flammability, it is important to avoid aggregation of the nanoparticles during melt mixing that, often, is a serious problem in POSS/polymer nanocomposites formulation. 14 The formation of a chemical bond between POSS nanoparticles and polymer backbone is an alternative route to successful incorporation, 15 and, usually, POSS-based homogeneous hybrid polymeric materials are prepared through the one-pot copolymerization method, i.e., POSS monomers and organic monomers mixed together prior to the polymerization process.…”
Section: Introductionmentioning
confidence: 99%
“…Polyhedral oligomeric silsesquioxanes (POSSs) are a class of hybrid inorganic–organic compounds with an inner inorganic framework made up of silicon and oxygen that is externally covered by various organofunctional derivatives, and their general formula is (RSiO 1.5 ) n , where n is an integer and R is an organic group. Studies concerning polymer/POSS nanocomposites have been reported extensively in the last decade . The dispersion states, homogenous dispersion or aggregation, of POSS in polymers strongly depend on the nature of the peripheries of POSS, which, subsequently, affects the decomposition temperature, as well as the mechanical properties of polymer/POSS nanocomposites.…”
Section: Introductionmentioning
confidence: 99%